1986
DOI: 10.1128/jcm.24.6.1017-1022.1986
|View full text |Cite
|
Sign up to set email alerts
|

Improved, computer-generated system for pyocin typing of Pseudomonas aeruginosa

Abstract: We applied numerical clustering algorithms to the selection of a new indicator strain set for the pyocin typing of Pseudomonas aeruginosa. The new indicator set is composed of selected indicator strains from the sets described in 1966 by Gillies and Govan (J. Pathol. Bacteriol. 91:339-345) and in 1974 by Jones, Zakanycz, Thomas, and Farmer (Appl. Microbiol. 27:400-406) and is designated the G-F set. This indicator set consists of 14 indicator strains which typed 99.5% of 114 test cultures, has a high degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Classic methods have mostly relied upon phenotypic traits. None of these techniques is capable of typing all strains, and each technique generally yields rather broad categories (4,14,17,19,20,24,32).…”
mentioning
confidence: 99%
“…Classic methods have mostly relied upon phenotypic traits. None of these techniques is capable of typing all strains, and each technique generally yields rather broad categories (4,14,17,19,20,24,32).…”
mentioning
confidence: 99%
“…Typing to evaluate the probability of cross‐transmission is commonly advised in epidemiological investigations, and the use of very discriminatory typing methods is recommended for differentiating epidemiologically unrelated isolates. It is widely accepted that traditional phenotypic methods of typing isolates of P. aeruginosa [5, 7, 8]do not permit accurate investigation of nosocomial infections because phenotypic markers are relatively unstable. In contrast, molecular subtyping methods offer high typeability and reproducibility, can define clonal relationships between isolates, and have contributed significantly to a better understanding of the epidemiology of P. aeruginosa infections [9–18, 21, 22, 25, 31].…”
Section: Discussionmentioning
confidence: 99%
“…This serotyping scheme characterizes most strains of P. aeruginosa possessing smooth LPS, although shows poor discrimination against rough LPS isolates which are common in patients with cystic fibrosis [5, 6]. Other conventional available systems based on phenotypic markers, such as biotyping, pyocin‐typing, phage‐typing, or antimicrobial susceptibility may not give satisfactory answers to basic epidemiological questions as they rely on the analysis of characteristics that are not stably expressed [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, during this period, it was found that R-type pyocins have a more efficient killing activity than headless mutants of a related phage, supporting the hypothesis that these particles are not simply defective prophages but evolved weapons ( Shinomiya and Shiga, 1979 ). Additionally, their advantage for medical use was explored, employing pyocins for P. aeruginosa typing ( Farmer and Herman, 1969 ; Rose et al, 1971 ; Edmonds et al, 1972 ; Lovrekovich et al, 1972 ; Jones et al, 1974 ; Duncan and Booth, 1975 ; Bruun et al, 1976 ; Fyfe et al, 1984 ; Schable et al, 1986 ) as well as a potential treatment against P. aeruginosa infections ( Merrikin and Terry, 1972 ; Haas et al, 1974 ). In addition to all these findings, a new type of phage tail-like pyocin, the F-type, was discovered ( Takeya et al, 1969 ; Govan, 1974b ; Kuroda et al, 1979 ; Kuroda and Kageyama, 1979 , 1981 ; Michel-Briand and Baysse, 2002 ; Saha et al, 2023 ).…”
Section: A Brief History Of Ecissmentioning
confidence: 99%